Penerapan Metode Kooperatif Tipe Number Heads Together (NHT) untuk Meningkatkan Hasil Belajar Siswa pada Tema 4 Sub Tema 1 Jenis-jenis Pekerjaan di Kelas IV MI NW Montong Mas - Helmi Najamudin; Wawan Mulyadi Purnama (Al-Munawwarah : Jurnal Pendidikan Islam, 2021)
The problem in this research is the low interest of students in learning Theme 4 Sub Theme 1 Types of Work in Class IV MI NW Montong Mas, low learning outcomes, teachers who do not motivate students or the learning process is less interesting and learning facilities are limited. The problem solving used to overcome this problem is by using the Number Heads Together (NHT) Cooperative learning model. The objectives of this research are 1). To find out the application of the Number Heads Together (NHT) cooperative method to learning outcomes 2). To determine learning planning using the Number Heads Together (NHT) model and 3). To find out the implementation of learning using the Number Heads Together (NHT) method. This study used classroom action research and was conducted in two cycles. Each cycle consists of four stages, namely planning, action, observation or observation, and reflection. Data collection is obtained through observation, tests and documentation. The subjects of this research were class IV students at MI NW Montong Mas for the 2020/2021 academic year. The variables in this research are student learning outcomes in theme 4 sub theme 1 types of work in class IV MI NW Montong Mas using the NHT type cooperative method. From the results of the analysis it was found that student learning outcomes in Theme 4 Sub Theme 1 Types of Work have increased, this is indicated by an increase in student learning completeness in each cycle, in cycle I (53.85%) meaning that classical completeness has not been achieved, and in cycle II (92.30%), meaning that classical learning completeness has been achieved. From the research results, it was concluded that the NHT learning model had a positive impact on improving the learning outcomes of class IV students at MI NW Montong Mas. It is recommended that it can be used as input or consideration for teachers, especially in Theme 4 Sub Theme 1 Types of Work, that NHT model learning needs to be implemented and developed.